2010
DOI: 10.1177/0047287510385467
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scale to Measure Memorable Tourism Experiences

Abstract: The quality experiences provided to customers, which are indeed memorable, directly determine a business's ability to generate revenue (Pine and Gilmore 1999). However, the extant tourism literature has provided limited explanation of the factors that characterize memorable tourism experiences. Thus, the goal of the present study was to develop a valid and reliable measurement scale that will assist in understanding the concept and in improving the effective management of the memorable experience. Following Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
1,072
5
86

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,079 publications
(1,212 citation statements)
references
References 97 publications
49
1,072
5
86
Order By: Relevance
“…As expected, tourism is one of the economic sectors that benefits most from experiential marketing, as has being demonstrated by recent works in different contexts [31][32][33][34]. These works confirm the power of experiential marketing in destinations promotion, and the relationship between the emotional and intellectual dimensions of visitor experiences, travel intentions, and destination loyalty.…”
Section: Experiential Marketingsupporting
confidence: 80%
See 2 more Smart Citations
“…As expected, tourism is one of the economic sectors that benefits most from experiential marketing, as has being demonstrated by recent works in different contexts [31][32][33][34]. These works confirm the power of experiential marketing in destinations promotion, and the relationship between the emotional and intellectual dimensions of visitor experiences, travel intentions, and destination loyalty.…”
Section: Experiential Marketingsupporting
confidence: 80%
“…The positive significant parameters obtained suggests that a high-richness destination image (β = 0.331) is very important in improving experience, as well as motivation (β = 0.299) and information (β = 0.172). In addition, and according to previous works in the field [21,25,26,29,30,32,33,38,50], the experience is dominated by internal emotions, although external conditions are also important for gaining a positive global experience abroad. In the Erasmus student case, our results revealed that cultural factors also significantly contribute to creating a great experience.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Correspondingly, in the development of a scale to measure memorable tourism experiences, Kim, Ritchie, and McCormick (2012) also showed the involvement factor on their scale dimension list. Again, no evidence was provided to suggest this factor's relationship to flow experience.…”
Section: Results Discussionmentioning
confidence: 97%
“…The tourism industry provides multi-dimensional and multifaceted experiences (Kim, Ritchie & Mccormick, 2012;Neuhofer, Buhalis & Ladkin, 2012). Researchers suggest that leisure experiences are about feeling, fantasy and fun (Holbrook & Hirschman, 1982), escape and relaxation (Beard & Ragheb, 1983), entertainment (Pine & Gilmore, 1999;Farber & Hall 2007), novelty and surprise (Dunman & Mattila, 2005).…”
Section: Gamification In Tourism Marketingmentioning
confidence: 99%